2017
DOI: 10.1177/0363546517738003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Prevention Program for Medial Elbow Injuries in Youth Baseball Players

Abstract: A prevention program aiming to improve physical function can prevent medial elbow injury in youth baseball players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 32 publications
2
93
0
Order By: Relevance
“…Some research has been performed on the relationship between hip ROM and throwing injuries among young baseball players. 10,26,27 Sakata et al 28 reported that a prevention program consisting of 9 stretching and 9 strengthening exercises could prevent elbow injury and improve several indicators of physical function, such as shoulder ROM and hip IR ROM, as well as thoracic kyphosis. A single cross-sectional study showed a significant association between medial elbow injury and hip IR ROM on the stride side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research has been performed on the relationship between hip ROM and throwing injuries among young baseball players. 10,26,27 Sakata et al 28 reported that a prevention program consisting of 9 stretching and 9 strengthening exercises could prevent elbow injury and improve several indicators of physical function, such as shoulder ROM and hip IR ROM, as well as thoracic kyphosis. A single cross-sectional study showed a significant association between medial elbow injury and hip IR ROM on the stride side.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,33 Some studies have reported a positive association between elbow and shoulder injuries and biomechanical dysfunction of the trunk and lower extremities (eg, lumbopelvic control, 7 hip ROM, 29 and foot posture 13 ) in adult baseball players. Although Sakata et al 28 suggested that a prevention program aiming to improve physical function can prevent elbow injuries, only a few studies have examined the relationship of physical dysfunction of the trunk and lower extremities with elbow and shoulder pain in young baseball players. 27,34 In our clinical experience, we have seen injured baseball players with biomechanical dysfunction such as hamstring tightness, hip ROM restriction, and scapular dysfunction.…”
mentioning
confidence: 99%
“…At the youth level, a preventive strengthening and stretching program reduced the risk of elbow injury in baseball players. 67 The program included stretching of the elbow, forearm, triceps, shoulder, lower thorax, trunk, and hip. Strengthening, posture, and balance exercises addressed the dominant rotator cuff, trapezius, scapular stabilization, and core.…”
Section: Prevention Of Injury Via Training and Rehabilitationmentioning
confidence: 99%
“…Whilst the thoracic spine does not feature strongly in the sporting literature for reasons including its relatively low pain prevalence and challenges with measurement, evidence supports the thoracic spine as playing a significant role in sporting performance, contributing to the estimated 55% of the total force and kinetic energy generated during a throw, around 80% of the total available range of “trunk” axial rotation, and kinematically important to the UL . With a three times higher elbow/ shoulder injury prevalence in softball players with low trunk rotation flexibility, and a beneficial effect of an UL injury prevention program including thoracic mobility exercises on shoulder/elbow injury prevalence, a greater focus on the thoracic spine, as a discrete region within the trunk and its contribution to UL function, is required. Whilst the concept of “regional interdependence” has contributed to notable growth in research investigating and supporting the use of interventions targeting an asymptomatic thoracic spine in patients with shoulder complaints, with ostensibly a neurophysiological relationship proposed, the nature of the kinematic relationship between the thoracic spine and shoulder or UL in an athletic population has not yet been fully established.…”
Section: Introductionmentioning
confidence: 99%